Certification of UK gastrointestinal endoscopists and variations between trainee specialties: results from the JETS e-portfolio - Siau, Keith; Anderson, John T.; Valori, Roland; Feeney, Mark; Hawkes, Neil D.; Johnson, Gavin; McKaig, Brian C.; Pullan, Rupert D.; Hodson, James; Wells, Christopher; Thomas-Gibson, Siwan; Haycock, Adam V.; Beales, Ian L.P.; Broughton, Raphael; Dunckley, Paul; on behalf of the Joint Advisory Group on Gastrointestinal Endoscopy (JAG) (Endoscopy International Open, 2019)
Introduction In the UK, endoscopy certification is administered by the Joint Advisory Group on Gastrointestinal Endoscopy (JAG). Since 2011, certification for upper and lower gastrointestinal endoscopy has been awarded via a national (JETS) e-portfolio to the main training specialties of: gastroenterology, gastrointestinal surgeons (GS) and non-medical endoscopists (NME). Trends in endoscopy certification and differences between trainee specialties were analyzed.Methods This prospective UK-wide observational study identified trainees awarded gastroscopy, sigmoidoscopy, colonoscopy (provisional and full) certification between June 2011 – 2017. Trends in certification, procedures and time-to-certification, and key performance indicators (KPIs) in the 3-month pre- and post-certification period were compared between the three main training specialties.Results Three thousand one hundred fifty-seven endoscopy-related certifications were awarded to 1928 trainees from gastroenterology (52.3 %), GS (28.4 %) and NME (16.5  %) specialties. During the study period, certification numbers increased for all modalities and specialties, particularly NME trainees. For gastroscopy and colonoscopy, procedures-to-certification were lowest for GS (P < 0.001), whereas time-to-certification was consistently shortest in NMEs (P < 0.001). A post-certification reduction in mean cecal intubation rate (95.2 % to 93.8 %, P < 0.001) was observed in colonoscopy, and D2 intubation (97.6 % to 96.2 %, P < 0.001) and J-maneuver (97.3 % to 95.8 %, P < 0.001) in gastroscopy. Overall, average pre- and post-certification KPIs still exceeded national minimum standards. There was an increase in PDR for NMEs after provisional colonoscopy certification but a decrease in PDR for GS trainees after sigmoidoscopy and full colonoscopy certification.Conclusion Despite variations among trainee specialties, average pre- and post-certification KPIs for certified trainees met national standards, suggesting that JAG certification is a transparent benchmark which adequately safeguards competency in endoscopy training.